Perceptions of politics and organizational justice on bank employees - Nurmalasari, Fitri; Suhariadi, Fendy; Subhekti, Erick Fajar (MBR (Management and Business Review), 2023)
This study aims to investigate the organizational politics perception of bank employees and its impact on organizational justice perception and performance. A comparative descriptive qualitative analysis method was used to analyze data obtained from literature review and field research. Purposive sampling technique was employed to determine 5 informants, with key informants being managers in a bank in Surabaya. The results showed that organizational politics in the bank is relatively high and has a negative impact on employees' organizational justice perception. The contribution of this research lies in providing a deeper understanding of organizational politics in the banking industry and offering guidance for management to enhance efficiency and the quality of the work environment.